Analisis Penerapan Dynamic Positioning pada PSV S Panglima Saat Cuaca Buruk - Devia Magfira; Eva Susanti; Andi Dirga Noegraha (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2026)
This study aims to analyze the implementation of the Dynamic Positioning (DP) system on the Platform Supply Vessel (PSV) S Panglima in dealing with adverse weather conditions during offshore operations. A descriptive qualistative method was employed, with data collected through direct observation, interviews with the Dynamic Positioning Operator (DPO), and documentation from the vessel’s Dynamic Positioning System (DPS). The results indicate that the Dynamic Positioning Class 2 system was able to maintain the vessel’s position effectively under wind speeds of up to 30 knots and wave heights of up to 3 meters, with an average position deviation of less than 3 meters and thruster utilization ranging from 75% to 95%. However, under extreme weather conditions, system performance declined due to sensor disturbances and increased propulsion loads. Manual intervention by the DPO using Hybrid Control mode proved effective in stabilizing the vessel’s position and preventing loss of position. Adverse weather conditions increased fuel consumption by up to 70% and reduced operational efficiency by approximately 12%; nevertheless, the DP system remained an effective solution for maintaining the vessel’s position without anchoring, thereby enhancing operational safety and efficiency at sea. The study concludes that the successful implementation of the DP system under severe weather conditions depends on sensor reliability, proper system maintenance, and operator competence. Therefore, routine sensor calibration, extreme weather simulation training for DPOs, and the integration of real-time weather monitoring systems are recommended to further improve Dynamic Positioning performance in offshore vessel operations.